Kobieta uczoną – droga Polek do samodzielności naukowej - Kolbuszewska , Jolanta (Studia Europaea Gnesnensia, 2019)
The text outlines the efforts of Polish women to be given access to academic education and, in consequence, scholarly career culminating in at least a post-doctoral degree. The author also presents data reflecting the number of women on the territory of Poland who obtained successive scientific degrees/titles, starting with doctorate, through a post-doctoral degree to full professors. To illustrate the data, the author cites specific examples of successful female careers in humanities and sciences. The timeframe spans the period from the turn of the 20th century to 1939.